Small bowel injury after suprapubic catheter insertion presenting 3 years after initial insertion. (10th December 2013) - Gallagher, Kevin M; Good, Daniel W; Brush, John P; Al-hasso, Ammar; Stewart, Grant D
Abstract : A 77-year-old woman was referred to urology with blockages of her suprapubic catheter (SPC). The catheter was replaced easily in the emergency department, however, no urine was draining, only a cloudy green fluid was visible. On cystoscopy bilious material was identified in the bladder. There was no catheter visible. There seemed to be a fistulous tract entering the bladder at the left dome. The urethra was dilated, a urethral catheter was placed and the SPC was removed. A CT demonstrated that the SPC tract transfixed a loop of pelvic small bowel and entered the bladder with no intraperitoneal contrast leak. The patient recovered well and did not require laparotomy. This case emphasises that bowel perforation, although rare, must be considered as a complication of SPC placement even years after initial insertion when catheter problems arise. Unusually, we learn that this complication may not present with abdominal pain or peritonism.